2004
DOI: 10.1086/423606
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular and Dust Envelope of HD 56126

Abstract: We present millimeter interferometry images of the CO J=1-0 line emission arising in the circumstellar envelope of HD 56126 (a.k.a. IRAS 07134+1005), which is one of the best studied 21-micron proto-planetary nebulae (PPNs). The CO emission extends from 1.2" to 7" in radius from the central star and appears consistent with a simple expanding envelope, as expected for a post-AGB star. We quantitatively model the molecular envelope using a radiative transfer code that we have modified for detached shells. Our be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 35 publications
9
40
0
Order By: Relevance
“…Some PPNs have been found to exhibit equatorial tori. For example, the dust continuum and CO map of the 21 µm source IRAS 07134+1005 suggests the presence of torus (Kwok, Volk, & Hrivnak 2002;Meixner et al 2004;Nakashima et al 2009). Tables 1 and Table 2 also give the fitting uncertainties of the feature strengths, which are estimated using the full covariance matrix of the least-squares parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Some PPNs have been found to exhibit equatorial tori. For example, the dust continuum and CO map of the 21 µm source IRAS 07134+1005 suggests the presence of torus (Kwok, Volk, & Hrivnak 2002;Meixner et al 2004;Nakashima et al 2009). Tables 1 and Table 2 also give the fitting uncertainties of the feature strengths, which are estimated using the full covariance matrix of the least-squares parameters.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the dust mass reported in Table 3 could be underestimated because the assumed dust opacity is derived from an approximated grain model with an average grain size of 0.1 µm Ref. 1, 2, 3, 4 5, 6, 7, 18, 19, 20 3, 8, 9, 10, 18, 19, 21 11, 12, 13, 19, 22 14, 15, 18, 19, 20 13, 16, 17, 18 References -(1) Meixner et al (2004); (2) …”
Section: Resultsmentioning
confidence: 99%
“…Their detailed radiative transfer model derived a circumstellar envelope mass of M H ∼ 0.16-0.44 M ⊙ , depending on the assumed gas-to-dust ratio (∼ 220-600). Meixner et al (2004) found a more extended envelope (with radius between 1.2 ′′ -7 ′′ ) based on their CO J = 1-0 line emission images. They derived a much smaller mass for the envelope (M H ∼ 0.059 M ⊙ ).…”
Section: Van Winckel and Reyniersmentioning
confidence: 95%